Suitability of rapeseedmustard varieties as a relay with t. aman rice: Relay cropping of mustard with T. Aman - Bhuiya, A A F; Baque, M A; Sakib, M N; Islam, F; Ahmed, F; Malek, M; Masum, SM; Hasanuzzaman, M (Bangladesh Journal of Agriculture, 2026)
A field experiment on T. Aman-mustard relay cropping was conducted at the Agronomy Research field of Sher-e-Bangla Agricultural University, Dhaka in 2023-2024 to identify the suitable short duration variety for relay with T. Aman. Ten varieties of rapeseed-mustard viz., Binasarisha-4, Binasarisha-9, Binasarisha-10, Binasarisha-11, BARI Sarisha-14, BARI Sarisha-15, BARI Sarisha-16, BARI Sarisha-17, BARI Sarisha-18, and BARI Sarisha-20 were evaluated as relay with T. Aman. The seeds of rapeseed-mustard were broadcasted in a standing T. Aman rice crop after the excess water drained out at 10 days before the rice harvest. The rice was harvested at 15 cm above the ground level. The experiment was conducted in a randomized complete block design with three replications. Results indicated that growth as well as yield contributing characteristics and seed yield of rapeseed-mustard were significantly varied among the varieties. The variety BARI Sharisa-16 produced the highest seed yield and followed a trend as BARI Sarisha-17 > BARI sharisa15 > BARI Sharisa-14 > BINA sarisha11. These varieties showed higher number of leaf plant-1, leaf area, leaf area index, 1000-seed weight, siliqua plant-1, and seeds siliquae-1.and took minimum days to flowering and. The seed yields of these varieties were significantly positively correlated with growth duration, and yield contributing attributes. Despite its high yield potential, farmers are not interested to cultivate mustard var. BARI Sarisha-16 as a relay crop with T. Aman rice due to its long growth duration. On the other hand, mustard var. BARI Sarisha-14, BARI Sarisha-15, BARI Sarisha-17, and Binasarisha-11 matured by 75-80 days, which were suitable as relay crop with T. Aman rice. Bangladesh J. Agri. 2025, 50(2): 69-84